Group sessions with Paro in a nursing home: Structure, observations and interviews. (9th June 2015) - Robinson, Hayley; Broadbent, Elizabeth; MacDonald, Bruce
Abstract : Aim: We recently reported that a companion robot reduced residents' loneliness in a randomised controlled trial at an aged‐care facility. This report aims to provide additional, previously unpublished data about how the sessions were run, residents' interactions with the robot and staff perspectives. Methods: Observations were conducted focusing on engagement, how residents treated the robot and if the robot acted as a social catalyst. In addition, 16 residents and 21 staff were asked open‐ended questions at the end of the study about the sessions and the robot. Results: Observations indicated that some residents engaged on an emotional level with Paro, and Paro was treated as both an agent and an artificial object. Interviews revealed that residents enjoyed sharing, interacting with and talking about Paro. Conclusion: This study supports other research showing Paro has psychosocial benefits and provides a guide for those wishing to use Paro in a group setting in aged care.